Regional Budget and Regional Development in Simalungun Regency: A Var Approach - Kristianto Kristianto; Desmi Triyanti Purba; Resna Napitu; Johan Alfred Sarades Silalahi; Agung Yuda Permana (Jurnal Ilmiah Accusi, 2026)
This study aims to determine the preparation and control of regional budgets in supporting regional development in Simalungun Regency and the use of the Vector Auto Regressive (VAR) Method to provide strategic recommendations in supporting regional development in Simalungun Regency. The research method used in this study is the VAR econometric method aimed at analyzing economic relationships using empirical data and statistical tools and this research design uses quantitative research with an econometric approach whose analysis emphasizes numerical data (numbers) processed by statistical methods. Data collection techniques used in this study are documentation and interviews. Based on the Impulse Response Function Analysis, the relationship between Regional Budget Preparation and Control on Regional Development is mutually influential, with temporary impacts before finally returning to stability. Therefore, budget preparation and control policies in Simalungun Regency must consider short-term and long-term impacts on regional development. More effective planning is needed to ensure that budget allocations not only support regional economic growth but also maintain fiscal balance in the long term